Designers' guide to Eurocode : basis of structural design, EN 1990 - Gulvanessian, H.; Calgaro, J. A.; Holický, Milan (ICE, 2012)
Annotation Eurocode 0 is considered the primary document in the Eurocode suite and establishes for the structural Eurocodes the principles and requirements for safety and serviceability of structures. More importantly, EN 1990 must be applied whenever the Eurocodes 1 to 9 are used.
Keywords: Structural design -- Standards -- European Union countries.; Buildings -- Standards -- European Union countries.; Eurocodes (Standards); elektronické knihy; electronic books